2012
DOI: 10.1016/j.foodchem.2011.10.110
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and evaluation of the antioxidant activity of phenolic constituents of the Garcinia brasiliensis epicarp

Abstract: A new glycosylated biflavonone, morelloflavone-4'″-O-β-d-glycosyl, and the known compounds 1,3,6,7-tetrahydroxyxanthone, morelloflavone (fukugetin) and morelloflavone-7″-O-β-d-glycosyl (fukugeside) were isolated from the epicarp of Garcinia brasiliensis collected in Brazil. The structures of these compounds were established using H andC NMR, COSY, gHMQC and gHMBC spectroscopy. The compounds exhibited antioxidant activity. The greatest potency was displayed by morelloflavone (2), with IC=49.5mM against DPPH and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(35 citation statements)
references
References 28 publications
2
30
0
3
Order By: Relevance
“…Vegetable as dietary sources contains significant amount of polyphenols that are responsible for multiple biological responses including antioxidant activity [37, 38]. In the present investigation extract showed dose dependent DPPH radical scavenging activity with the IC 50 value of 158.52 μg/mL.…”
Section: Discussionmentioning
confidence: 50%
“…Vegetable as dietary sources contains significant amount of polyphenols that are responsible for multiple biological responses including antioxidant activity [37, 38]. In the present investigation extract showed dose dependent DPPH radical scavenging activity with the IC 50 value of 158.52 μg/mL.…”
Section: Discussionmentioning
confidence: 50%
“…In this context, G. brasiliensis has been extensively studied as a source of these compounds. It is emphasized that Santa-Cecília et al (2011) and Gontijo et al (2012) identified the phenolic derivatives Gutipherone-A, 7-epyclusianone and the bioflavonoids moreloflavone (fukugetin), moreloflavone-7"O-β-D glycol (fukugeside) and moreloflavone-4"O-β-D glycol in extracts from fruit and leaf of G. brasiliensis. They also evaluated antioxidant, antinociceptive and anti-inflammatory activities of extracts and isolated compounds showing the pharmacological potential of these substances.…”
Section: Discussionmentioning
confidence: 99%
“…NMR spectra were measured on a multinuclear FT-NMR spectrometer (Bruker AVANCE DRX-400 or Bruker AVANCE DPX-200 MHz and DRX-500 MHz). (Gontijo et al, 2012a), (±)-Fukugiside (compound 2) (Elfita et al, 2009) and morelloflavone (compound 3) (Li et al, 2002).…”
Section: General Considerationsmentioning
confidence: 99%